2015
DOI: 10.1002/2014wr016737
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of evapotranspiration using high‐frequency water vapor isotopic measurement over a rice paddy field

Abstract: Partitioning ecosystem evapotranspiration (ET) into soil evaporation (E) and transpiration (T) is crucial for understanding hydrological processes. In this study, by using high-frequency isotope measurements and continuous surface water measurements, we investigated the isotope ratios in soil-vegetationatmosphere transfer and the physical mechanisms involved over a paddy field for a full growing season. The isotopic signals of d ET , d T , and d E were determined by the Keeling plot method, surface water isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 63 publications
10
90
3
1
Order By: Relevance
“…Rothfuss et al (2010) showed a larger uncertainty range of 2%-74%, suggesting that using different values of kinetic fractionation factor in the Craig-Gordon model results in a large range of un certainties, though uncertainties also come from mea surement errors. For example, the uncertainty in isotopic compositions of shallow soil water can signifi cantly affect the accuracy (Rothfuss et al 2010;Wei et al 2015). For the leaf-water isotope-based method, the uncertainties mainly come from leaf sampling pre cision as it has large differences in isotopic composition in different leaf sites, and there is obvious diurnal vari ation in leaf isotopic compositions (Flanagan and Ehleringer 1991;Wang et al 2012;Welp et al 2008).…”
Section: B the Uncertainty O F Partitioning Results And Comparison Wmentioning
confidence: 99%
See 3 more Smart Citations
“…Rothfuss et al (2010) showed a larger uncertainty range of 2%-74%, suggesting that using different values of kinetic fractionation factor in the Craig-Gordon model results in a large range of un certainties, though uncertainties also come from mea surement errors. For example, the uncertainty in isotopic compositions of shallow soil water can signifi cantly affect the accuracy (Rothfuss et al 2010;Wei et al 2015). For the leaf-water isotope-based method, the uncertainties mainly come from leaf sampling pre cision as it has large differences in isotopic composition in different leaf sites, and there is obvious diurnal vari ation in leaf isotopic compositions (Flanagan and Ehleringer 1991;Wang et al 2012;Welp et al 2008).…”
Section: B the Uncertainty O F Partitioning Results And Comparison Wmentioning
confidence: 99%
“…Variable eK is the kinetic fractionation factor defined by Eq. (8) (Cappa et al 2003;Wei et al 2015):…”
Section: ) Mass Balance Equations To Partition Etmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the partition of water transport, recent studies (e.g., Jasechko et al, 2013;Good et al, 2015;Wei et al, 2015) have explored the dominant role of transpiration in ecosystem evapotranspiration. The results of this work partially concur with these studies.…”
Section: Discussionmentioning
confidence: 99%